The Lexicon of Emoji? Conventionality Modulates Processing of Emoji. Issue 4 (1st April 2023) - Weissman, Benjamin; Engelen, Jan; Baas, Elise; Cohn, Neil
Abstract: Emoji have been ubiquitous in communication for over a decade, yet how they derive meaning remains underexplored. Here, we examine an aspect fundamental to linguistic meaning‐making: the degree to which emoji have conventional lexicalized meanings and whether that conventionalization affects processing in real‐time. Experiment 1 establishes a range of meaning agreement levels across emoji within a population; Experiment 2 measures accuracy and response times to word‐emoji pairings in a match/mismatch task. In this experiment, we found that accuracy and response time both correlated significantly with the level of population‐wide meaning agreement from Experiment 1, suggesting that lexical access of single emoji may be comparable to that of words, even out of context. This is consistent with theories of a multimodal lexicon that stores links between meaning, structure, and modality in long‐term memory. Altogether, these findings suggest that emoji can allow a range of entrenched, lexicalized representations.